Assessing Bias in Cognitive Testing for Older Adults with Sensory Impairment: An Analysis of Differential Item Functioning in the Baltimore Longitudinal Study on Aging (BLSA) and the Atherosclerosis Risk in Communities Neurocognitive Study (ARIC-NCS). (26th February 2022) - Nichols, E.; Deal, J.A.; Swenor, B.K.; Abraham, A.G.; Armstrong, N.M.; Carlson, M.C.; Griswold, M.; Lin, F.R.; Mosley, T.H.; Ramulu, P.Y.; Reed, N.S.; Resnick, S.M.; et al.
Abstract: Objectives: : Vision and hearing impairments affect 55% of people aged 60+ years and are associated with lower cognitive test performance; however, tests rely on vision, hearing, or both. We hypothesized that scores on tests that depend on vision or hearing are different among those with vision or hearing impairments, respectively, controlling for underlying cognition. Methods: : Leveraging cross-sectional data from the Baltimore Longitudinal Study of Aging (BLSA) and the Atherosclerosis Risk in Communities Neurocognitive Study (ARIC-NCS), we used item response theory to test for differential item functioning (DIF) by vision impairment (better eye presenting visual acuity worse than 20/40) and hearing impairment (better ear .5–4 kHz pure-tone average > 25 decibels). Results: : We identified DIF by vision impairment for tests whose administrations do not rely on vision [e.g., Delayed Word Recall both in ARIC-NCS: .50 logit difference between impaired and unimpaired ( p = .04) and in BLSA: .62 logits ( p = .02)] and DIF by hearing impairment for tests whose administrations do not rely on hearing [Digit Symbol Substitution test in BLSA: 1.25 logits ( p = .001) and Incidental Learning test in ARIC-NCS: .35 logits ( p = .001)]. However, no individuals had differences between unadjusted and DIF-adjusted measures of greater than the standard error of measurement. Conclusions: : DIF by sensory impairment in cognitive tests was independent of administration characteristics, which could indicate that elevated cognitive load among persons with sensory impairment plays a larger role in test performance than previously acknowledged. While these results were unexpected, neither of these samples are nationally representative and each has unique selection factors; thus, replication is critical.